1999
DOI: 10.1007/bf02318380
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic function in patients with chronic fatigue syndrome

Abstract: Subtle signs of autonomic dysfunction and orthostatic intolerance have been reported in patients with chronic fatigue syndrome (CFS). To assess cardiovascular autonomic function noninvasively in an unselected group of patients with CFS, we examined responsiveness to several cardiovascular reflex tests in 37 CFS patients and 38 healthy control subjects. Blood pressure and heart rate (HR) were recorded continuously by a Finapres device before and during forced breathing, standing up, Valsalva maneuver, and susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 32 publications
3
19
1
Order By: Relevance
“…This is in accordance with other studies showing low vagal tone [112,[118][119][120] and a general sympathetic overactivity [105,121,122]. However, there are also reports on decreased heart rate in response to exercise [123] or mental stress [124], or no differences between CFS and healthy controls at all [104,121,124]. A previous study [125] has shown increased salivary alpha-amylase (which is thought to reflect sympathetic activation) activity in CFS patients compared to healthy controls, both at baseline and after a psychosocial stress test in the laboratory.…”
Section: Findings On Ans and Cfssupporting
confidence: 90%
“…This is in accordance with other studies showing low vagal tone [112,[118][119][120] and a general sympathetic overactivity [105,121,122]. However, there are also reports on decreased heart rate in response to exercise [123] or mental stress [124], or no differences between CFS and healthy controls at all [104,121,124]. A previous study [125] has shown increased salivary alpha-amylase (which is thought to reflect sympathetic activation) activity in CFS patients compared to healthy controls, both at baseline and after a psychosocial stress test in the laboratory.…”
Section: Findings On Ans and Cfssupporting
confidence: 90%
“…Another study demonstrated impaired HR responses indicating the existence of attenuated cardiac sympathetic responsiveness. These lower HR responses could not be reconciled with an explanation based on patient deconditioning or prolonged inactivity [19]. Those authors reported that hemodynamic responses in patients with ME/CFS were significantly impaired during exercise compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…[34] detected a sympathetic drive mediated increased heart rate on tilt compared to healthy controls. Another study demonstrated impaired heart rate responses to exercise coupled with globally impaired hemodynamic responses incompatible with patient deconditioning or prolonged inactivity [35]. Several other authors have reported autonomic dysfunctions in people with ME/CFS [36-38].…”
Section: Phenomenological Similarities Between Sickness Behavior and mentioning
confidence: 99%